Teaching Writing with Authentic Video through SWELL Method for EFL Students - Rasmi (Eduvelop: Journal of English Education and Development, 2023)
This research with a quantitative method aims to examine whether the use of authentic videos is effective to improve students’ writing ability of third semester students at English Tadris Program. The population in this research were students at the third semester students at English Tadris Program and the sample was students of TBI 1 and 2 with total sample of 56 students. In this research the researcher used a total sampling technique. And the data collection technique using test, namely pre-test and post-test. The technique of data analysis that the researcher used is the t-test. The results of the data analysis showed that t-count is and t-table (t-count 7.175 > t-table 1.184). It means the results of the research showed that there is a significant improvement of the students’ writing ability of the third semester students’ writing skill after the use of authentic video through SWELL Method of third semester students at English Tadris Program.